We Need to Talk About Rationing: The Need to Normalize Discussion About Healthcare Rationing in a Post COVID-19 Era - Bhatia, Neera (J Bioeth Inq, 2020)
The global COVID-19 pandemic has brought the issue of rationing finite healthcare resources to the fore. There has been much academic debate, media attention, and conversation in the homes of everyday individuals about the allocation of medical resources, diagnostic testing kits, ventilators, and personal protective equipment. Yet decisions to prioritize treatment for some individuals over others occur implicitly and explicitly in everyday practices. The pandemic has propelled the socially taboo and unavoidably prickly issue of healthcare rationing into the public spotlight—and as such, healthcare rationing demands ongoing public attention and transparent discussion. This article concludes that in the aftermath of COVID-19, policymakers should work towards normalizing rationing discussions by engaging in transparent and honest debate in the wider community and public domain. Further, injecting greater openness and objectivity into rationing decisions might go some way towards dismantling the societal taboo surrounding rationing in healthcare.